The Gold Standards Framework Hospital programme: implementation and progress. (2nd April 2022) - Thomas, Keri; Armstrong-Wilson, Julie; Clifford, Collette
Abstract : Aim: The implementation and impact of the Gold Standards Framework Hospitals (GSFH) service development programme is described. Background: A third of hospital inpatients may be in their last year of life when admitted to hospital. Many will be repeat and unplanned admissions. National policy guidance seeks to change this pattern through implementing patient choice in end-of-life care (EOLC) planning. Method: GSFH training and resources help general hospital staff teams develop skills as they identify patients nearing the end of life, rapidly assess their needs and offer advance care planning (ACP). Findings: Audit data shows teams that have undergone GSFH training demonstrate earlier identification of patients needing EOLC and offer ACP targeting their individual care needs. Conclusion: The model has been taken up by over 350 hospital wards, with a large number seeking accreditation to demonstrate sustainability of good practice in EOLC management.